Action Coordination in Non-Human Self-Organizing Collectives: Multidisciplinary Lessons From Living and Nonliving Systems. Issue 4 (1st October 2020) - Chiovaro, Megan; Paxton, Alexandra
Abstract: While interpersonal coordination, collective intelligence, and self-organization have been fundamental in the study of human social interaction over the past several decades, these phenomena have a rich history in non-human systems as well. This special issue aims to unite disciplines studying inter-entity coordination of action in shared conversation. Here, we bring together ecological psychologists, ecologists, biologists, neuroethologists, and chemists, all working toward understanding the fundamentals of group coordination. We believe that contact among these different perspectives is essential for continuing to expand the impact of the ecological perspective to other fields. While this multidisciplinary special issue takes an explicitly non-human view of collective behavior, we hope it will not only improve our basic understanding of inter-entity dynamics but also spark curiosity and inspire new approaches in the study of human collectives.